Factors affecting the reproductive performance of Boran (Bos indicus) cows in a single-sire mating system - Tegegne, Azage; Entwistle, K.W.; Mukasa-Mugerwa, E. (1993)
A total of 179 heifers, primiparous and multiparous Boran cows were assigned to four breeding units and mated over a 4 - month breeidng season in a single-sire mating system. Mean body weight and body condition scores at the beginning of mating ranged from 363 + 6 kg to 388 + 7 kg and from 6.7 + 0.1 to 7.0 + 0.1 in the four breeding units, respectively. Body weight losses in cows in the four breeding units ranged from 8 to 35kg over the mating period, losses being higher in lactating cows (44 kg) than in non-lactating cows (6 kg). Pregnancy rates ranged from 81 to 94 percent in the four breeding units and were not influenced by lactation status. First calf heifers had the lowest pregnancy rate with a tendency for increasing pregnancy rates with parity in multiparous cows. Lactating cows calved later (P<0.05) than did non-lactating cows, and heifers calved later (P<0.05) than cows. A smaller percentage of heifers (43 percent) than multiparous cows (64 percent) calved during the first two calving months. There was no significant correlation between body weight, weight changes, or calf growth performances, and pregnancy rate and calving patterns.